Um retrato sobre os caminhos do óleo de cozinha utilizado (residual) em restaurantes na cidade de Bagé-RS - (:unkn) unknown (Universidade Federal do Pampa, 2015)
This study aims to characterize the activity in restaurants, to identify the classification of types of waste based on the laws involved, finding the rating for the cooking oil residue used, as well as specifying the law of Bage -RS municipality related with cooking oil residue used as its final destination, and identify the organizational practices adopted by the restaurants in the disposal of cooking oil in the process. The results through a data collection (interview and forms drawn up based on legislation and documents of Bage-RS Prefecture) with a few restaurants in the city of Bage-RS were well satisfactory and are in accordance with the proposed objectives. Thus we identified several information gaps, and from the analysis of the results , along with some opinions of participants in the data collection , it was proposed some actions and / or solutions for the future of Bage -RS , as well as for future work addressing the issue presented here.
Keywords: Engenharia da produção; Destinação final; Restaurante; Legislação ambiental; Óleo de cozinha; Práticas organizacionais; Production engineering; Final destination; Restaurant; Environmental legislation; Cooking oil; Organizational practices